2016
DOI: 10.1590/s0100-736x2016001200010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of somatic cells derived from ear tissue of collared peccary (Pecari tajacu Linnaeus, 1758) in medium with different requirements

Abstract: The maintenance of metabolic activities during the in vitro culture of somatic cells of wild animals, especially collared peccary (Pecari tajacu), is an interesting step in conservation of these cells for the use in nuclear transfer. In this context, it is necessary to optimize the culture conditions of somatic cells by the establishment of appropriate supplementation to the media. Therefore, this study aimed to analyze the composition of the culture means of somatic cell derived from ear tissue of collared pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…In this sense, studies related to the conservation of the collared peccary have been intensified, especially aimed at improving the techniques related to the preservation of somatic samples. Using this study, we established a culture condition for explants derived from the skin of adult collared peccaries (Santos et al, 2016) and developed a protocol for cryopreservation (Borges et al, 2017(Borges et al, , 2018a(Borges et al, , 2018b) and refrigeration of these explants (Queiroz Neta et al, 2018). In order to conduct the cloning experiments on this species by a somatic cell nuclear transfer, as well as to produce induced pluripotent cells, it is necessary to establish properly characterized cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies related to the conservation of the collared peccary have been intensified, especially aimed at improving the techniques related to the preservation of somatic samples. Using this study, we established a culture condition for explants derived from the skin of adult collared peccaries (Santos et al, 2016) and developed a protocol for cryopreservation (Borges et al, 2017(Borges et al, , 2018a(Borges et al, , 2018b) and refrigeration of these explants (Queiroz Neta et al, 2018). In order to conduct the cloning experiments on this species by a somatic cell nuclear transfer, as well as to produce induced pluripotent cells, it is necessary to establish properly characterized cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed environment of the cells (Guo et al, 2018), we observed previously (Santos et al, 2016) that the medium for growth of somatic cells derived from collared peccaries was DMEM with 10% FBS and 2% antibiotic-antimycotic solution.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, in the management of systems of the collared peccaries, their identification is recorded by ear sections and these fragments (1-2cm 2 ) were recovered for the experiment. Then, skin tissues were transported to the laboratory in Dulbecco modified Eagle medium (DMEM) with 2.2g/L sodium bicarbonate and 2% antibiotic-antimycotic solution at 37°C for 30 min, according to Santos et al (2016). At the laboratory, the tissue fragments were washed in 70% ethanol and DMEM.…”
Section: Methodsmentioning
confidence: 99%